Healthcare Providers and Parents Highlight Challenges of Pediatric Hand Fracture Care. Issue 2 (17th February 2023) - Lafreniere, Ann-Sophie; Baykan, Altay; Hartley, Rebecca; Ronksley, Paul; Love, Shannan; Harrop, Alan Robertson; Fraulin, Frankie O.G.; Campbell, Dave J.T.; Donald, Maoliosa
Abstract : Background: Pediatric hand fractures are common, and many are referred to hand surgeons despite less than 10% of referrals requiring surgical intervention. We explored healthcare provider and parent perspectives to inform a new care pathway. Methods: We conducted a qualitative descriptive study using virtual focus groups. Emergency physicians, hand therapists, plastic surgeons, and parents of children treated for hand fractures were asked to discuss their experiences with existing care for pediatric hand fractures, and perceptions surrounding the implementation of a new care pathway. Data were analyzed using directed content analysis with an inductive approach. Results: Four focus groups included 24 participants: 18 healthcare providers and six parents. Four themes were identified: educating parents throughout the hand fracture journey, streamlining the referral process for simple hand fractures, identifying the most appropriate care provider for simple hand fractures, and maintaining strong multidisciplinary connections to facilitate care. Participants described gaps in the current care, including a need to better inform parents, and elucidated the motivations behind emergency medicine physicians' existing referral practices. Participants also generally agreed on the need for more efficient management of simple hand fractures that do not require surgical care. Healthcare providers believed the strong preexisting relationship between surgeons and hand therapists would facilitate the changes brought forward by the new care pathway. Conclusion: These findings highlighted shortcomings of existing care for pediatric hand fractures and will inform the co-development and implementation of a new care pathway to enable more efficient management while preserving good patient outcomes.